Concerns for Sustainability: Integration of Natural Resource and Environmental Issues in the Research Agenda of NARS - Crosson, Pierre; Anderson, Jock R. (International Service for National Agricultural Research, 1993)
Achievement of sustainable agricultural systems requires farm technologies and management practices that indefinitely accommodate increasing demand for food and fiber at economic and environmental costs consistent with rising per capital welfare of people. To achieve sustainable agricultural systems in this sense the national agricultural research systems (NARS) in the less-developed countries must systematically integrate into their research agenda the effects of new technologies and practices on the natural resource base and environment. The concept of total productivity is useful in addressing this task because it can be defined to include all the benefits of new technology on the output side—both marketed commodities and unmarketed environmental services—and all the costs on the input side, including natural resource depletion and environmental damage. Changes in per capita total productivity over time thus provide an indicator of the sustainability of the new technologies developed through NARS research. The key problem in constructing measures of total productivity is the difficulty of measuring the unpriced environmental benefits and costs of new technologies. The physical processes by which the impacts are transmitted through the environment often are poorly understood. Assigning values to the impacts is problematic because they are not registered in markets, hence are unpriced. The capacity of most NARS to effectively incorporate natural resource and environmental issues in their research agenda also is problematic. Current NARS staffing reflects their commitment to traditional commodity research, which gives relatively little weight to natural resource and environmental impacts. They are particularly short of the social science skills they will need to give these impacts the weight they must have to assure agricultural sustainability. It is critically important that NARS strengthen their capacity to do the needed research. Absent this capacity, they will fall short of their responsibility to put their countries' agriculture on a sustainable path. Moreover, they will risk loss of control of the agricultural research agenda to other more aggressive institutions and groups that, in the interest of environmental protection, may underestimate the importance of increasing production of food and fiber.